Older Adults’ Engagement in Senior University Lectures and the Effect of Individual Motivations - Ackermann, Tobias Peter; Seifert, Alexander (Frontiers in Education, 2021)
Among older adults, engagement in education can potentially have positive effects on cognition and psychological well-being and can prevent social isolation. The aim of this study is to investigate the role of individual motivations specific to older learners that underlie the frequency of participation at a senior university and how health or socioeconomic dimensions may affect the possibilities for participation. With data on participants from the senior university program at the University of Zurich (N = 811), we show that greater individual motivations regarding different aspects of learning have an effect on the frequency of lecture attendance, while other life circumstances do not. However, the findings show that when different forms of motivations are compared, instrumental motivation—meaning that the intention to use the gained knowledge now or in the future is responsible for the participant’s learning aspirations—is the only motivation that significantly increases lecture attendance. Hence, we conclude that to increase people’s engagement in this specific form of education in later life and to intensify lecture attendance, these programs should meet the expectations fueled by individual motivations.